Injury prevention in child and adolescent sport: whose responsibility is it? - Emery, C.; Hagel, B.; Morrongiello, B. (Clinical Journal of Sport Medicine, 2006)
Objective: Sport and recreational injuries are a leading cause of morbidity in youth. There is a significant body of literature on risk factors for sport-related injuries and a growing body of research supporting the effectiveness of sport-specific prevention strategies in youth. Given the predictability and preventability of injuries in youth sport, the purpose of this article is to develop a model that considers societal responsibility for injury prevention in youth sport, and to discuss the evidence that supports this model.